Japanese attitudes toward cell donation in human brain organoid research: many oppose broad consent - Kataoka, Masanori; Koike, Mayu; Sawai, Tsutomu (Frontiers in Genetics, 2025)
IntroductionUnder broad consent, donors are not informed about the specific research projects using their cells; this may lead to the use of cells in ways that conflict with donors' moral beliefs. In recent years, this issue has been raised in human brain organoid research. However, previous studies on the public’s attitude toward human brain organoid research have either overlooked cell donation or consisted of small-scale qualitative studies.MethodsWe conducted an online survey on Japanese citizens' attitudes toward cell donation for human brain organoid research, gathering 326 responses.ResultsWhen informed that donated cells could generate human brain organoids, 36% of participants disapproved of broad consent, while 37% said their stance depended on the case. Reasons for opposition included the need for study-specific explanations, autonomous decision-making, emotional discomfort, research purpose, researchers' and institutional trustworthiness, potential misuse, and risks and benefits to participants.DiscussionAlthough several limitations exist, these findings may suggest that project-specific consent would be more ethically appropriate at the current stage of human brain organoid research. Since some public concerns stem from limited knowledge or misinformation, science communication could help change this situation.